POTENSI ZAKAT, INFAQ, SHODAQOH PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) DI KABUPATEN BANYUWANGI - Abdul Kholiq Syafa’at; Lely Ana Ferawati Ekaningsih (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The purpose of this study is to analyze accountability BAZNAS Banyuwangi, Knowing the constraints of ZIS management, as well as analyzing Muzaki and Mustahiq Perception. The data is analyzed in descriptive qualitative point of view. Based on the potential survey of Zakat in 2013 of zakat profession basic salary of civil servants from the data BKD until November 18, 2013, the number of government employees– 13.058 people– can be calculated using the assumption of civil servants who fulfill the obligation to pay the ZIS by 85% of the total employees with basic salary charged at the rate of 2.5% zakat then projected potential zakat fund which will be managed by BAZNAS during 2013 was Rp. 10,359,735,300 per year, so there is a possibility to increase the potential number of muzakis and ZIS for next year